DINAMIKA GENDER DI AREA URBAN INDONESIA: SEBUAH EKSPLORASI TENTANG PERAN PROFESIONAL DAN DOMESTIK DI TAMALANREA, MAKASSAR - Rukmana Syafrin, Novayanti Sopia; Syam, Febrianto (SOSIORELIGIUS, 2024)
Indonesia, characterized by its rich cultural diversity, grapples with gender equality challenges, particularly evident in urban contexts like Tamalanrea, Makassar, especially within the Bumi Tamalanrea Permai residential complex. Gender, defined by societal norms and traditions that demarcate roles between men and women, ideally promotes equality rather than discrimination. Despite progressive strides in numerous urban regions, the deep-seated patriarchal culture in certain communities remains a barrier to positive transformation. This study explores two main areas: the impact of male dominance in the job sector on the opportunities, rewards, and treatment of women, especially those with families; and the dynamics of decision-making within households, which is often male-dominated, and its effects on relationship quality, responsibility distribution, and the emergence of various forms of violence. Through a comprehensive analysis, this research aims to shed light on gender imbalances and their repercussions on women's professional and domestic roles in Indonesia.